Covid‐19 in patients with hematological and solid cancers at a Comprehensive Cancer Center in Germany. (15th September 2020) - Shoumariyeh, Khalid; Biavasco, Francesca; Ihorst, Gabriele; Rieg, Siegbert; Nieters, Alexandra; Kern, Winfried V.; Miething, Cornelius; Duyster, Justus; Engelhardt, Monika; Bertz, Hartmut
Abstract: Background: Patients with cancer are considered a high‐risk group for viral pneumonia, with an increased probability of fatal outcome. Here, we investigated the clinical characteristics and outcome of patients with solid and hematological cancers and concomitant Covid‐19 at a Comprehensive Cancer Center in a Covid‐19 hotspot area in Germany. Methods: We performed a retrospective single center cohort study of 39 patients with hematological and solid cancers who were hospitalized at the University Hospital Freiburg for Covid‐19. Using univariate and multivariate Cox regression models we compared time to severe events and overall survival to an age‐matched control cohort of 39 patients with confirmed Covid‐19 without a cancer diagnosis. Results: In the cancer cohort 29 patients had a diagnosis of a solid tumor, and 10 had a hematological malignancy. In total, eight patients (21%) in the cancer and 14 patients (36%) from the noncancer cohort died during the observation period. Presence of a malignancy was not significantly associated with survival or time to occurrence of severe events. Major influences on mortality were high IL‐6 levels at Covid‐19 diagnosis (HR = 6.95, P  = .0121) and age ≥ 65 years (HR = 6.22, P  = .0156). Conclusions: Compared to an age‐matched noncancer cohort, we did not observe an association between a cancer diagnosis and a more severe disease course or higher fatality rate in patients with Covid‐19. Patients with a hematological malignancy showed a trend towards a longer duration until clinical improvement and longer hospitalization time compared to patients with a solid cancer. Cancer per se does not seem to be a confounder for dismal outcome in Covid‐19. Abstract : In this retrospective single center cohort study at a Comprehensive Cancer Center in Germany we did not observe an association between a cancer diagnosis and a more severe disease course or higher fatality rate in patients with Covid‐19 when compared to an age‐matched control cohort of patients with confirmed Covid‐19 without a cancer diagnosis.